2011
DOI: 10.1029/2011gl049095
|View full text |Cite
|
Sign up to set email alerts
|

Impact of ocean acidification on benthic and water column ammonia oxidation

Abstract: [1] Ammonia oxidation is a key microbial process within the marine N-cycle. Sediment and water column samples from two contrasting sites in the English Channel (mud and sand) were incubated (up to 14 weeks) in CO 2 -acidified seawater ranging from pH 8.0 to pH 6.1. Additional observations were made off the island of Ischia (Mediterranean Sea), a natural analogue site, where long-term thermogenic CO 2 ebullition occurs (from pH 8.2 to pH 7.6). Water column ammonia oxidation rates in English Channel samples decr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

5
61
1

Year Published

2013
2013
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 73 publications
(67 citation statements)
references
References 32 publications
5
61
1
Order By: Relevance
“…cessation of ammonia oxidation at pH 6.5 (Kitidis et al 2011). In artificially acidified lakes, Rudd et al (1988) also observed the complete shutdown of nitrification at pH below 5.7.…”
Section: Introductionmentioning
confidence: 86%
“…cessation of ammonia oxidation at pH 6.5 (Kitidis et al 2011). In artificially acidified lakes, Rudd et al (1988) also observed the complete shutdown of nitrification at pH below 5.7.…”
Section: Introductionmentioning
confidence: 86%
“…Recently, we have shown [8] that for several different sediment types a reduction in seawater pH had no effect upon ammonia oxidation rates in surface sediments, in contrast to the reduction in rates observed within the corresponding overlying water samples. We suggested two reasons for this discrepancy: firstly, that the dissolution of carbonate minerals within the sediment may act to buffer the pore water pH, minimizing the effect of OA, and/or, secondly, that a change in the structure of microbial nitrifying communities occured within the sediment, favouring bacteria or archaea that are more tolerant of low-pH conditions [8].…”
mentioning
confidence: 82%
“…both in situ and experimental studies covering a range of pH values (from 6.0 to approx. 8.10) [6][7][8][9].…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies were focused either in predicting the effects of future pH reduction or investigating the biogeochemical outcomes of coastal pH decline on certain organisms' response/survival or merely on the processes ultimately determining CO 2 fate and impact in aquatic systems (e.g. Andersson et al, 2007;Kitidis et al, 2011;Widdicombe et al, 2009;Laverock et al, 2014). Marine systems however, constitute of specific features, more complex than simple chemical or thermodynamic equilibria which are necessary, nonetheless, for any calculation or prediction model.…”
Section: Discussionmentioning
confidence: 99%